2022
DOI: 10.48550/arxiv.2205.15484
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prospects of a thousand-ion Sn$^{2+}$ Coulomb-crystal clock with sub-$10^{-19}$ inaccuracy

Abstract: We propose a many-ion optical atomic clock based on three-dimensional Coulomb crystals of order one thousand Sn 2+ ions confined in a linear RF Paul trap. Sn 2+ has a unique combination of features that is not available in previously considered ions: a 1 S0 ↔ 3 P0 clock transition between two states with zero electronic and nuclear angular momentum (I = J = F = 0) making it immune to nonscalar perturbations, a negative differential polarizability making it possible to operate the trap in a manner such that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…The experiment allows us to characterize the VUV source for laser spectroscopy and demonstrates that the source can be used for the excitation of the isomer in 229 Th. We note that there is also considerable interest in laser excitation of trapped ions of other elements in this wavelength range, for example for proposed optical clocks with Pb 2+ [8] and Sn 2+ [9] or for laser cooling of Al + [10]. Similar techniques like the ones demonstrated here may be employed in those cases.…”
Section: Introductionmentioning
confidence: 84%
“…The experiment allows us to characterize the VUV source for laser spectroscopy and demonstrates that the source can be used for the excitation of the isomer in 229 Th. We note that there is also considerable interest in laser excitation of trapped ions of other elements in this wavelength range, for example for proposed optical clocks with Pb 2+ [8] and Sn 2+ [9] or for laser cooling of Al + [10]. Similar techniques like the ones demonstrated here may be employed in those cases.…”
Section: Introductionmentioning
confidence: 84%
“…As the ratio between the anharmonic and harmonic terms typically increases when the ion-electrode distance is reduced, it is demonstrated that anharmonic effects become more critical by lessening the ion trap scale. This requires special care, particularly in the case of single-ion [90,105,106] and multi-ion optical clocks [74,91,107,108] or in quantum sensing [109] and quantum computing experiments with trapped ions [65,110]. On the other hand, it is demonstrated that an increased dodecapole potential generated in an asymmetric LIT [99] opens new pathways for exciting applications in mass spectrometry or Coulomb crystals.…”
Section: Introductionmentioning
confidence: 99%
“…Continued efforts on these clocks will presumably be rewarded with even lower systematic uncertainties. Alternatively, other atomic systems could offer unprecedented levels of clock accuracy [7][8][9][10]. One intriguing candidate is 229 Th 3+ .…”
mentioning
confidence: 99%